Voluntary Intake and Digestibility of Nutrients in Heifers Fed Hydroponics Maize (Zea mays L.) Fodder - Naik, P.K.; Karunakaran, M.; Swain, B.K.; Chakurkar, E.B.; Singh, N.P. (Indian Journal of Animal Nutrition, 2018)
Voluntary intake and digestibility of nutrients in heifers fed hydroponics maize (Zea maize L.) fodder was studied. Hydroponics maize fodder (HMF) was produced in a hydroponics chamber (greenhouse) measuring about 25 ft Ã— 10 ft Ã— 10 ft with a daily production potential of 600 kg fresh HMF and equipped with automatic sprayer irrigation by tap water. Four heifers (avg. BW 305 kg) were fed individually 2 kg standard conventional concentrate mixture along with 3 kg jowar straw and ad lib. HMF daily to meet their nutrientÂ requirements for a period of 45 days followed by a 6-d digestion trial. The HMF looked like a mat of 20-30 cm height consisting of germinated seeds, white roots and green leaves. The increase in weight of the HMF than the seed weight on fresh basis was 5-6 folds. The DM content of the HMF was 15.4% and the CP, EE, CF, NFE and TA content was 13.56, 2.46, 8.98, 73.45 and 1.56% on DM basis, respectively. The DM intake per 100 kg BW of the heifers was 2.25 and the R: C ratio was maintained at 73: 27. The digestibility of DM, OM, CP, EE, CF and NFE of the ration was 65.62, 68.06, 69.36, 80.95, 59.70 and 69.87%, respectively. The total ration had 12.73% CP, 8.81% DCP and 68.71% TDN. It can be concluded that hydroponics maize fodder could be fed to heifers in situations where conventional fodder is not available or can not be grown due to any adverse conditions.